A new method for early warning of dangerous rock collapse based on tilt and vibration parameters. Issue 6 (October 2021) - Xie, M W; He, Z; Ying, Y Y; Lu, G; Sun, G C; Wang, J
Abstract: Dangerous rock refers to an unstable rock block that is cut by weak structural planes and gradually separates from the slope, and at present, it is challenging to effectively identify the separation degree of dangerous rock and accurately warn of its sudden failure. In this paper, a microelectromechanical system (MEMS) acceleration sensor is used in combination with the calculation principle of the included angle of the space vector to establish an integrated monitoring method of the microtilt angle and strong vibration acceleration (SVA). Through long-term field monitoring, the tilt angle and the SVA information of the whole collapse process are obtained. The analysis results show that (1) the tilt-time curve of dangerous rock is of the step-type, and the continuous and rapid increase of the tilt rate is a deformation precursor characteristic of a collapse; (2) in the absence of strong vibration source disturbance, the SVA is an early identification parameter for dangerous and stable rock, and the abnormal increase of triggering frequency of the SVA is the vibration precursor characteristic of a collapse; (3) three warning modes of dangerous rock based on the tilt rate and the SVA are obtained, i.e., stable mode, perturbation mode and alarm mode. This study provides an important early warning indicator for rock collapse.